Intralesional Spesolimab: A Novel and Effective Approach for Palmoplantar Pustulosis Treatment – A Case Report - Wang SN; Lu YZ; Zhao Y; Cao W; Zhang RL (International Medical Case Reports Journal)
Si-Ning Wang,* Yi-Zhou Lu,* Yujuan Zhao, Wei Cao, Rui-Li Zhang Department of Dermatology, The Second Affiliated Hospital Nanjing Medical University, Nanjing Medical University, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rui-Li Zhang, Department of Dermatology, The Second Affiliated Hospital of Nanjing Medical University, Nanjing Medical University, Nanjing, 210003, People’s Republic of China, Email rellyzhang@njmu.edu.cnAbstract: Palmoplantar pustulosis (PPP) is a chronic condition characterized by the presence of sterile pustules on the palms and soles of the feet. As we all know, there is currently no gold standard for the treatment of this intractable disease. Currently, interleukin-36 receptor (IL-36R)-targeted biologics are emerging as promising treatments for PPP. Here, we were the first to report a Chinese male with PPP who received an intralesional injection of spesolimab. We found that only a small intralesional injection volume of spesolimab could effectively suppress PPP in this case.Keywords: Palmoplantar pustulosis, spesolimab, intralesional injection, case report